Marketing Trends on Tempeh-based Products between 2018-2025 - Wildan Guretno Prasetiyo; Yasmin Fathimah Farid (International Journal of Marketing & Human Resource Research, 2026)
Tempeh sales in Indonesia experienced significant fluctuations and decline from 2018 to 2024 driven by rising soybean prices and shifting youth preferences toward foreign cuisine. This trend negatively impacts MSME profitability and contradicts national food sovereignty missions known as Asta Cita. Consequently, this study aims to analyze market trends and the research landscape regarding tempeh derivatives and their marketing aspects. The study employed bibliometric analysis following PRISMA 2020 guidelines. Data were retrieved from Web of Science and Google Scholar databases resulting in a final dataset of 2,095 articles analyzed using VOSviewer software. The findings indicate that Indonesia is the leading contributor to scholarly output with IPB University as the dominant institution. Research themes are anchored on raw tempeh followed by tempeh chips and tempeh flour. SWOT Analysis is the most utilized marketing method with Price and Product Quality as the primary variables. The dominant market segments are plant-based meat followed by plant-based protein and healthy food. Geographically Malang alongside Semarang and Surabaya are identified as the primary productive regions. These insights provide an empirical foundation for MSMEs to develop product innovations targeting the plant-based meat and healthy food segments thereby supporting the green economy and national food sovereignty goals.